Pengaruh Kinerja Keuangan dan Ukuran Perusahaan terhadap Harga Saham dengan Kebijakan Dividen sebagai Variabel Intervening pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Handayani, Karunia Mei; Indarti, Iin; Listiyowati, Listiyowati (Jurnal Ilmiah Aset, 2019)
This study was conducted to examine the effect of leverage ratio, activity ratio and firm size on company’s stock price with dividend policy as the intervening variable in manufacturing companies listed in Indonesia Stock Exchange in 2015-2017. This study had a population of 420 companies and a total sample of 114 companies. The sampling technique used purposive sampling. The first regression results showed that Debt to Equity Ratio, Total Asset Turn Over, Firm Size partially did not affect Dividend Policy. The second regression result of Debt to Equity Ratio, Dividend Policy had no effect on Stock Price, Total Asset Turn Over had a positive effect on Stock Price, Firm Size had a negative effect on Stock Price. Debt to Equity Ratio (X1), Total Asset Turn Over (X2), Size (X3) affected Dividend Policy by 1.1% and Debt to Equity Ratio (X1), Total Asset Turn Over (X2), Firm Size ( X3), Dividend Policy (Y2) affected Stock Price of 9.9%. The mediation test results showed that Dividend Policy is proven to mediate the relationship of Total Asset Turn Over and Firm Size on Stock Price, while Debt to Equity Ratio on Stock Price cannot be mediated by Dividend Policy.